Health financing, health outcomes and economic growth in developed and developing countries - Omer, Abdalla Sirag Fagir (2016)
Sufficient health financing is important due to the precious value of health. Across the world, there exist large variations in health financing due the differences in many factors such as income level. In addition, health outcome is directly affected by health financing, income, education, and indirectly by the level of governance (governance quality). Moreover, economic growth is largely influenced by better health outcome,since healthier individuals tend to be more productive and learn faster. The current research aims to estimate the determinants of public health financing and out-of-pocket health expenditure in 181 countries from 1995 to 2012. The second objective examines the impact of public health financing and out-of-pocket health financing on health outcomes, particularly on infant and under-five mortality rates and life expectancy, in 172 countries. Also, the indirect effect of health financing through governance quality is tested. The Generalized Method of Moments is used to estimate the dynamic models in both first and second objectives. Moreover, the third objective aims to examine the non-linear relationship between life expectancy and economic growth, and public health financing and economic growth in developed and developing countries from 1981 to 2010 using the Dynamic Panel Threshold estimator.The findings show that the GDP per capita and general government expenditure are crucial factors that affect health financing in low-income, middle-income, and highincome countries. Interestingly, external aid for health is found to have positive impact on public health financing in low-income countries, whereas it reduces public health financing in middle-income countries. The findings indicate that the external health funding tends to reduce public health financing, especially when it is received by a country with low governance quality. Remarkably, a high level of government effectiveness and control of corruption are found to be very influential in stimulating public health financing and helping to reduce out-of-pocket health financing in developed and developing countries.Regarding the second objective, the results reveal that public health financing plays a decisive role in stimulating health outcomes in developed and developing countries.However, the non-linear effect for health financing on health outcomes is observed,especially when health is financed by individuals’ out-of-pocket expenditure. In particular, the out-of-pocket health expenditure found to be negatively related to health outcomes in low-income and middle-income countries, whereas it positively associated with health outcomes in high-income countries. In addition, the findings reveal the importance of socioeconomic factors such as income and education as key determinants of health outcomes. Further, the analysis of this study shows that governance quality positively correlated to health outcomes through its effect on public health financing. Finally, the findings of the third objective contribute to economic growth literature by providing new evidence on the relationship between health and economic growth. The results indicate the existence of non-linear relationship between life expectancy and growth. In particular, life expectancy is useful to economic growth only to a certain threshold level; any further increase in longevity above the threshold would adversely affect growth. Furthermore, the findings show that public health financing has a nonlinear effect on economic growth. Specifically, public health spending is beneficial to growth until a certain threshold level, above the threshold point, however; public health expenditure impedes economic growth.For policymakers, greater efforts are needed to ensure the efficiency of public finances and health care systems in both developed as well as developing countries. The findings provide future insights for developing countries, and a chance to avoid the potential turning point by reforming their health systems.